2015
DOI: 10.1039/c4an02007c
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement and quantitation of 4-hydroxyphenylacetic acid and dopamine with fast-scan cyclic voltammetry

Abstract: Caged compounds have been used extensively to investigate neuronal function in a variety of preparations, including cell culture, ex vivo tissue samples, and in vivo. As a first step toward electrochemically measuring the extent of caged compound photoactivation while also measuring the release of the catecholamine neurotransmitter, dopamine, fast-scan cyclic voltammetry at carbon-fiber microelectrodes (FSCV) was used to electrochemically characterize 4-hydroxyphenylacetic acid (4HPAA) in the absence and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…Figure 3A shows a CV of 4HPAA (0.1 mM) obtained by flow injection analysis and FSCV. As described by Shin et al, 30 we observed two well-resolved peaks, suggesting that two distinct electrochemical processes occur. The first peak occurred at +1.23 V as the potential swept toward the most positive value, while the second peak occurred at +1.12 V as the potential swept toward the most negative value.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Figure 3A shows a CV of 4HPAA (0.1 mM) obtained by flow injection analysis and FSCV. As described by Shin et al, 30 we observed two well-resolved peaks, suggesting that two distinct electrochemical processes occur. The first peak occurred at +1.23 V as the potential swept toward the most positive value, while the second peak occurred at +1.12 V as the potential swept toward the most negative value.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…We have previously shown that 4HPAA can readily be measured by FSCV. 30 Thus, we sought here to demonstrate that the liberation of 4HPAA from p-hydroxyphenacyl-based caged compounds, such as p-hydroxyphenacyl glutamate, could be used to quantify the formation of the resulting bioactive molecule. Our approach quantifies glutamate photorelease by measuring differences between currents produced by the liberation of 4HPAA after light application and currents present prior to light application.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations